(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
In Uzbekistan, the development of the mahalla, its socio-economic and cultural advancement, as well as the revival of national customs and traditions, have been identified as priority objectives. Since ancient times, local people have lived within the framework of family, neighborhood, mahalla, and community relations. Along with being a small administrative unit, the mahalla can also be understood as a community of people united by a shared way of life, values, traditions, and customs. This article examines the mahalla as a center of national and religious values. It analyzes national and religious values that have been formed within the mahalla environment over centuries, including peace, social harmony, kindness, compassion, etiquette of greeting, and respect for the elderly.